Mouth rinsing with carbohydrate solutions at the postprandial state fail to improve performance during simulated cycling time trials - Ispoglou, T.; O'Kelly, D.; Angelopoulou, A.; Bargh, M.; O'Hara, J. P.; Duckworth, L. C. (The Journal of Strength and Conditioning Research, 2015)
Mouth rinsing with carbohydrate (CHO) solutions during cycling time trials results in performance enhancements; however, most studies have used approximately 6% CHO solutions. Therefore, the purpose of this study was to compare the effectiveness of mouth rinsing with 4, 6, and 8% CHO solutions on 1-hour simulated cycling time trial performance. On 4 occasions, 7 trained male cyclists completed at the postprandial period, a set amount of work as fast as possible in a randomized counterbalanced order. The subjects rinsed their mouth for 5 seconds, on completion of each 12.5% of the trial, with 25 ml of a non-CHO placebo and 4, 6, and 8% CHO solutions. No additional fluids were consumed during the time trial. Heart rate (HR), ratings of perceived exertion (RPE), thirst (TH), and subjective feelings (SF) were recorded after each rinse. Furthermore, blood samples were drawn every 25% of the trial to measure blood glucose and blood lactate concentrations, whereas whole-body CHO oxidation was monitored continuously. Time to completion was not significant between conditions with the placebo, 4, 6, and 8% conditions completing the trials in 62.0 ± 3.0, 62.8 ± 4.0, 63.4 ± 3.4, and 63 ± 4.0 minutes, respectively. There were no significant differences between conditions in any of the variables mentioned above; however, significant time effects were observed for HR, RPE, TH, and SF. Post hoc analysis showed that TH and SF of subjects in the CHO conditions but not in the placebo were significantly increased by completion of the time trial. In conclusion, mouth rinsing with CHO solutions did not impact 1-hour cycling performance in the postprandial period and in the absence of fluid intake. Our findings suggest that there is scope for further research to explore the activation regions of the brain and whether they are receptive to CHO dose, before specific recommendations for athletic populations are established. Consequently, mouth rinsing as a practical strategy for coaches and athletes is questionable under specific conditions and should be carefully considered before its inclusion. Emphasis should be focused on appropriate dietary and fluid strategies during training and competition.